1955 Multimodal critical discourse analysis of current representations of hearing loss in the UK news media - Fawcett-Jones, S; Heffernan, E; Putland, E; Broome, E; Burgon, C; Janani, A; Dening, T; Straus, J; Henshaw, H (Age and ageing, 2024)
Introduction Hearing loss (HL) affects 12 million UK adults, including 70% of those aged over 70 years. It is associated with social isolation, anxiety, and depression. Furthermore, HL in midlife is the largest modifiable risk factor for dementia. However, many individuals delay or avoid treatment. This may be due to limited understanding of HL amongst the public, and the considerable stigma surrounding HL and hearing aids. The media play a crucial role in shaping public perceptions of age-related conditions. Therefore, this study investigated representations of HL in UK newspapers, especially representations of the relationship between HL and mental health. Method Using Nexis (a news database), 7173 newspaper articles featuring HL between May 2022-May 2023 were retrieved. Following screening, 20 articles were analysed using multimodal critical discourse analysis. This qualitative approach regards communicative choices (here, images and text) as able to both reflect and shape society, including propagating or challenging stigma. A Patient and Public Involvement (PPI) panel contributed to study design and data interpretation. Results Most articles featured young adults with HL, particularly celebrities. Whilst this could challenge the stereotype that HL only affects older adults, it could also increase the invisibility of older adults in the media. Many articles contained inspirational stories, which may help reduce the stigma of HL. However, some people with HL do not want to be portrayed differently to other people. Some articles discussed HL and mental health, especially its association with dementia, loneliness, and depression. PPI contributors indicated that newspapers should provide diverse HL representations and should help improve public awareness of this condition, especially its impact on mental health. Discussion This research has important implications for clinicians, researchers, charities, the media, and all those who communicate with the public about HL. Future research should investigate HL representations in other media, particularly social media.